A mathematical model for suppression subtractive hybridization - Gadgil, Ch.; Rink, A.; Beattie, C.; Hu, W.
Suppression subtractive hybridization (SSH)is frequently used to unearth differentially expressed genes on a whole-genome scale. Its versatility is based on combining cDNA library subtraction and normalization, which allows the isolation of sequences of varying degrees of abundance and differential expression. SSH is a complex rocess with many adjustable parameters that affect the outcome of gene isolation.We present a mathematical model of SSH based on DNA hybridization kinetics for assessing the effect of various parameters to facilitate its optimization. We derive an equation for the probability that a particular differentially expressed species is successfully isolated and use this to quantify the effect of the following parameters related to the cDNA sample: (a)mRNA abundance; (b)partial sequence complementarity to other species; and (3)degree of differential expression. We also evaluate the effect of parameters related to the process, including: (a)reaction times; and (b)extent of driver excess used in the two hybridization reactions. The optimum set of process parameters for successful isolation of differentially expressed species depends on transcript abundance. We show that the reaction conditions have a significant effect on the occurrence of false-positives and formulate strategies to isolate pecific subsets of differentially expressed genes. We also quantify the effect of non-specific hybridization on the false-positive results and present strategies for spiking cDNA sequences to address this problem.
Keywords: SUPPRESSION SUBTRACTIVE HYBRIDIZATION; MATHEMATICAL MODEL; HYBRIDIZATION KINETICS